Analisis Kesalahan Penulisan Arab (Imla’iyyah) pada Siswa Madrasah Tsanawiyah - Arifin, Sultan; Muklishin, Muklishin; Syafi’i, Ahmad Helwani (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study investigates the forms and causes of Arabic writing errors (imlā’iyyah) among students at MTs Darul Qur’an Bengkel in West Lombok. The background of this research is the persistence of spelling problems in Arabic learning, especially in writing skills that require accuracy in letters, harakāt, and hamzah. The study aims to identify dominant error patterns and analyze the pedagogical and linguistic factors contributing to these errors. Using a descriptive qualitative approach, the subjects of this study were students and Arabic teachers at MTs Darul Qur’an Bengkel. The data consisted of students’ written texts, classroom observation results, and interview data, all derived from students and teachers. Data were collected through classroom observation, documentation of student writing, and interviews with teachers and students, and analyzed using descriptive qualitative analysis techniques: data reduction, data display, and conclusion drawing. The findings show several recurring errors, including confusion between similar letters, omission of harakāt, incorrect placement of hamzah, and missing dots. These errors are influenced by limited practice, interference from Latin script, insufficient understanding of basic qawā‘id, and unstable student motivation. The study concludes that systematic and continuous imlā’ training, the use of visual media, and error-based instruction can significantly improve students’ Arabic writing accuracy. Recommendations are provided for developing structured learning modules and strengthening literacy programs at the madrasah.